Differentiation of oncocytoma from chromophobe renal cell carcinoma (RCC): can novel molecular biomarkers help solve an old problem?. Issue 2 (29th October 2013) - Ng, Keng Lim; Rajandram, Retnagowri; Morais, Christudas; Yap, Ning Yi; Samaratunga, Hema; Gobe, Glenda C; Wood, Simon T
Abstract : Standard treatment of renal neoplasms remains surgical resection, and nephrectomy for localised renal cell carcinoma (RCC) still has the best chance of cure with excellent long-term results. For smaller renal masses, especially stage T1a tumours less than 4 cm, nephron-sparing surgery is often employed. However, small incidentally detected renal masses pose an important diagnostic dilemma as a proportion of them may be benign and could be managed conservatively. Renal oncocytoma is one such lesion that may pose little risk to a patient if managed with routine surveillance rather than surgery. Additionally, lower-risk RCC, such as small chromophobe RCC, may be managed in a similar way, although with more caution than the renal oncocytomas (RO). The ability to differentiate ROs from chromophobe RCCs, and from other RCCs with a greater chance of metastasis, would guide the physician and patient towards the most appropriate management, whether nephron-sparing surgical resection or conservative surveillance. Consistent accurate diagnosis of ROs is likely to remain elusive until modern molecular biomarkers are identified and applied routinely. This review focuses on the differentiation of renal oncocytomas and chromophobe RCCs. It summarises the history, epidemiology and clinical presentation of the renal neoplasms, explains the diagnostic dilemma, and describes the value, or not, of current molecular markers that are in development to assist in diagnosis of the renal neoplasms.